POSISI STRATEGIS KEPALA SEKOLAH DALAM MEMBANGUN MANAJEMEN KESISWAAN DAN SDM DI LEMBAGA PENDIDIKAN ISLAM MODERN - Fikria Aulia, Farina; Fadla Robbi; Muhamad Yasin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Modern Islamic educational institutions face complex challenges in the era of globalization and digitalization that demand professional and value-based institutional management. This study aims to examine the strategic position of school principals in developing student management and human resource management (HRM) in modern Islamic educational institutions through a library research approach. The findings reveal three main conclusions: first, school principals possess a multidimensional EMASLIM role grounded in Islamic values such as amanah, adalah, and syura; second, effective student management encompasses a holistic student affairs cycle integrating tarbiyah and ta'lim values at every stage; third, optimal HRM requires a comprehensive management cycle encompassing recruitment, competency development, academic supervision, and value-based performance evaluation. This study concludes that the integration of strategic principal leadership, structured student management, and value-based HRM constitutes an inseparable unified system in realizing modern Islamic educational institutions that are excellent and globally competitive.